2017
DOI: 10.1097/bsd.0b013e3182aab266
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlordosis is Associated With Facet Joint Pathology at the Lower Lumbar Spine

Abstract: STUDY DESIGN:: A retrospective study. OBJECTIVE:: Our study opted to clarify the remaining issues of lumbar lordosis (LL) in regard to (1) its physiologic values, (2) age, (3) gender, (4) facet joint (FJ) arthritis and orientation using CT scans. SUMMARYOF BACKGROUND DATA:: Recent studies have questioned whether LL really decreases with age, but study sample sizes have been rather small and mostly been based on X-rays. Since hyperlordosis increases the load transferred through the FJs, it seems plausible that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Hyperlordosis is considered to cause low back pain because of the increase in pressure on the posterior ligaments and facet joints 5,9 . In a CT analysis study, Jentzsch et al found that hyperlordosis of the lumbar spine was associated with facet joint arthritis in the lower lumbar spine 10 . Furthermore, Sorensen et al reported that lumbar lordosis in individuals who had low back pain when standing was greater than it was in individuals without low back pain 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlordosis is considered to cause low back pain because of the increase in pressure on the posterior ligaments and facet joints 5,9 . In a CT analysis study, Jentzsch et al found that hyperlordosis of the lumbar spine was associated with facet joint arthritis in the lower lumbar spine 10 . Furthermore, Sorensen et al reported that lumbar lordosis in individuals who had low back pain when standing was greater than it was in individuals without low back pain 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Beside these factors, and others related to the variability of the lumbar spine as subject of study—number of vertebrae used, pathological or nonpathological spines, presence or absence of lumbosacral transitional vertebrae, presence or absence of scoliosis, and so forth, discrepancies found among studies of sexual dimorphism and population variation could also stem from differences in the inclusion/exclusion criteria used by each author, which are often based on the sample's age range. Some consider age‐related degeneration to have an influence on the lumbar curvature—either increasing it (Jentzsch et al, ) or decreasing it (Dreischarf et al, ; Gelb, Lenke, Bridwell, Blanke, & McEnery, ; Korovessis et al, ; Merrill et al, ; Pries et al, )—and prefer to choose a younger‐aged sample in order to eliminate its effect in studies where age variation is not the main subject of study (Bailey et al, ). On the contrary, other authors do not find any relation between lordosis and age (Kalichman et al, ), and thus do not make any exclusions regarding age.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the degree of lumbar lordosis varies greatly throughout an individual's life history—during postnatal ontogeny, the lumbar lordosis is established and reaches its initial adult configuration shortly after puberty (Reichmann & Lewin, ; Shefi et al, ). During adulthood, the lumbar lordosis can change further with the senescence process (Dreischarf et al, ; Jentzsch, Geiger, König, & Werner, ; Korovessis, Stamatakis, & Baikousis, ; Pries, Dreischarf, Bashkuev, Putzier, & Schmidt, ). These changes are closely related to factors such as bone and soft tissue degeneration (Bogduk, ), genetic make‐up variability in different populations (i.e., inter‐population variation) and sexual dimorphism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations